Mucosal and systemic immune effects of Bacillus subtilis in rainbow trout (Oncorhynchus mykiss). Issue 124 (May 2022) - Docando, F.; Nuñez-Ortiz, N.; Serra, C.R.; Arense, P.; Enes, P.; Oliva-Teles, A.; Díaz-Rosales, P.; Tafalla, C.
Abstract: Bacillus spp. are well known for their probiotic properties. Hence, the long-term feeding of Bacillus spp. strains to different fish species has been proved to confer beneficial effects regarding growth or pathogen resistance, among others. However, whether these strains could function as mucosal adjuvants, up-regulating immune responses after a single administration, has not yet been investigated in fish. Thus, in the current work, we have performed a series of experiments in rainbow trout ( Oncorhynchus mykiss ) aimed at establishing the potential of two Bacillus subtilis spore-forming strains, designated as ABP1 and ABP2, as oral adjuvants/immunostimulants. As an initial step, we evaluated their transcriptional effects on the rainbow trout intestinal epithelial cell line RTgutGC, and in gut tissue explants incubated ex vivo with the two strains. Their capacity to adhere to RTgutGC cells was also evaluated by flow cytometry. Although both strains had the capacity to modulate the transcription of several genes related to innate and adaptive immune responses, it was the ABP1 strain that led to stronger transcriptional effects, also exerting a higher binding capacity to intestinal epithelial cells. Consequently, we selected this strain to establish its effects on splenic B cells upon in vitro exposure as well as to determine the transcriptional effects exerted in the spleen, kidney, and gut after a single oral administration of the bacteria. Our results showed that B. subtilis ABP1 had the capacity to modulate the proliferation, IgM secreting capacity and MHC II surface expression of splenic B cells. Finally, we confirmed that this strain also induced the transcription of genes involved in inflammation, antimicrobial genes, and genes involved in T cell responses upon a single oral administration. Our results provide valuable information regarding how B. subtilis modulates the immune response of rainbow trout, pointing to the usefulness of the ABP1 strain to design novel oral vaccination strategies for aquaculture. Highlights: Bacillus subtilis regulates the transcription of many immune genes in epithelial cells and gut explants. B. subtilis ABP1 strain has a higher adhesive capacity to trout intestinal epithelial cells than the ABP2 strain. B. subtilis ABP1 increased the proliferation, IgM secreting capacity and MHC II surface expression of splenic B cells. A single oral administration of ABP1 affected the transcription of a wide range of immune genes locally and systematically.